High‐order plate bending analysis based on the scaled boundary finite element method. (3rd June 2013) - Man, H.; Song, C.; Xiang, T.; Gao, W.; Tin‐Loi, F.
SUMMARY This paper presents a technique for plate bending analysis based on the scaled boundary FEM. The proposed technique is formulated directly from the three‐dimensional governing equations. The in‐plane dimensions of the plate are modelled by two‐dimensional finite elements. The solution along the thickness is expressed analytically as a Padé expansion by using the scaled boundary FEM. A simple and highly efficient procedure to construct the stiffness matrix of a thin to moderately thick plate element is devised. Furthermore, the use of high‐order spectral elements allows the proposed technique to accurately handle plates with curved boundaries and leads to high accuracy and convergence rate. Five plate bending problems are presented with results showing high computational efficiency. No numerical locking arises. Copyright © 2013 John Wiley & Sons, Ltd.